MILLENNIAL GENERATION CONSUMPTION BEHAVIOR IN THE USE OF E-COMMERCE IN THE DIGITAL ERA (CASE STUDY : UNIVERSITY STUDENT IN - Galuh Eka Pramithasari (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2017)
Technology’s development in this modern era experiencing rapid growth. In Indonesia, the development of internet itself has been growing rapidly. As a result, there are many positive impact in human’s life from the development of technology, with no exception by millennial generation. Millennial generation using internet almost in every aspect of their life including buying and selling activity via E-Commerce. Main purpose of this research is to analyze variable that affecting millennial generation consumption behavior, which represent by university student in Malang. The result showed that price (X1), lifestyle(X2), Convenience(X3), and trust(X50 has positive impact in university’s student consumption behavior(Y) while media information(X4) is the only one that has negative impact. Based on this result it can be concluded that consumption behavior of University student in Malang is very affected by price of goods, lifestyle of the student, Convenience of using E-Commerce and trust while advertisement of E-Commerce via media information has no impact on comsumption behavior.Keyword : millennial generation, consumption behavior, e-commerce